Use of linear features by red-legged partridges in an intensive agricultural landscape: implications for landscape management in farmland - Perrot, Charlotte; Seranne, Léo; Berceaux, Antoine; Noël, Mathias; Arroyo, Beatriz; Bacon, Léo (Peer Community Journal)

(untitled)
Current agricultural practices and change are the major cause of biodiversity loss. An important change associated with the intensification of agriculture in the last 50 years is the spatial homogenization of the landscape with substantial loss of such biodiversity-rich elements as seminatural linear features (hedgerows, field margins, grassy strips, etc.). In Europe, some management prescriptions serve to increase heterogeneity by the creation of these seminatural linear features which are not being used primarily for agricultural production. However, these elements are not equal in their support for biodiversity according to their structure and composition. The aim of this study is to determine the importance of landscape heterogeneity and specifically linear features on the spatial distribution of red-legged partridges, a small game species in decline in Europe. Through GPS-monitoring of adult birds, we first assess home range size throughout the year and during the breeding season, in relation to breeding status and to linear features (seminatural linear vegetation and tracks-roads for human traffic) density. Then, we focus on habitat selection during the breeding period in relation to linear features. We found that linear elements shape the use of space by red-legged partridges according to their reproductive status. Traffic routes and seminatural features structured by both herbaceous and woody cover, negatively influenced home range size. Further, breeding birds select linear elements with herbaceous cover while non-breeders select linear elements with woody cover, underlining the different needs of birds according to their breeding status. All birds selected areas near tracks, but non-breeders seemed to avoid roads. This study shows the importance for this species of the linear components that structure the agricultural landscape. We propose recommendations to promote the presence of the red-legged partridge in this agricultural environment but also of the biodiversity in general.